Incremental value of copeptin to highly sensitive cardiac Troponin I for rapid rule-out of myocardial infarction. (1st July 2015) - Wildi, Karin; Zellweger, Christa; Twerenbold, Raphael; Jaeger, Cedric; Reichlin, Tobias; Haaf, Philip; Faoro, Jonathan; Giménez, Maria Rubini; Fischer, Andreas; Nelles, Berit; Druey, Sophie; Krivoshei, Lian; et al.
Abstract: Background: The incremental value of copeptin, a novel marker of endogenous stress, for rapid rule-out of non-ST-elevation myocardial infarction (NSTEMI) is unclear when sensitive or even high-sensitivity cardiac troponin cTn (hs-cTn) assays are used. Methods: In an international multicenter study we evaluated 1929 consecutive patients with symptoms suggestive of acute myocardial infarction (AMI). Measurements of copeptin, three sensitive and three hs-cTn assays were performed at presentation in a blinded fashion. The final diagnosis was adjudicated by two independent cardiologists using all clinical information including coronary angiography and levels of hs-cTnT. The incremental value in the diagnosis of NSTEMI was quantified using four outcome measures: area under the receiver-operating characteristic curve (AUC), integrated discrimination improvement (IDI), sensitivity and negative predictive value (NPV). Early presenters (< 4 h since chest pain onset) were a pre-defined subgroup. Results: NSTEMI was the adjudicated final diagnosis in 358 (18.6%) patients. As compared to the use of cTn alone, copeptin significantly increased AUC for two (33%) and IDI (between 0.010 and 0.041 (all p < 0.01)), sensitivity and NPV for all six cTn assays (100%); NPV to 96–99% when the 99th percentile of the respective cTnI assay was combined with a copeptin level of 9 pmol/l (all p < 0.01). The incremental value in early presenters was similar to that of the overall cohort. Conclusion: When used for rapid rule-out of NSTEM in combination with sensitive or hs-cTnI assays, copeptin provides a numerically small, but statistically and likely also clinically significant incremental value. Highlights: Copeptin provides significant incremental diagnostic value in three of four outcome variables (IDI, sensitivity, and NPV) for hs-cTnI assays. Copeptin provides significant incremental diagnostic value in all four outcome variables (also AUC) for two sensitive cTnI assays. The main benefit of copeptin seems to be in the rule-out of AMI with an increase in sensitivity and NPV at the time of patient presentation.